2010
DOI: 10.1002/hbm.20966
|View full text |Cite
|
Sign up to set email alerts
|

Working memory for vibrotactile frequencies: Comparison of cortical activity in blind and sighted individuals

Abstract: In blind, occipital cortex showed robust activation to non-visual stimuli in many prior functional neuroimaging studies. The cognitive processes represented by these activations are not fully determined, although a verbal recognition memory role has been demonstrated. In congenitally blind and sighted (10 per group) we contrasted responses to a vibrotactile one-back frequency retention task with 5s delays and a vibrotactile amplitude-change (A–C) task; both tasks involved the same vibration parameters. The one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 98 publications
(135 reference statements)
9
36
0
Order By: Relevance
“…The response to language is strongly left lateralized. By contrast, responses during nonverbal tasks are bilateral or right lateralized (44,45). Consistent with this idea, we found neuroanatomically distinct patterns of response to backward speech and language in the occipital cortex.…”
Section: Discussionsupporting
confidence: 86%
“…The response to language is strongly left lateralized. By contrast, responses during nonverbal tasks are bilateral or right lateralized (44,45). Consistent with this idea, we found neuroanatomically distinct patterns of response to backward speech and language in the occipital cortex.…”
Section: Discussionsupporting
confidence: 86%
“…It could be that Braille reading proficiency etihanced the capability of the blind participants tested in Forster et al's study to focus their attention on a flngertip, in order to select the information at the relevant locations and ignore that at the nearby locations. This finding adds to the results of neuroimaging studies showing that sustained focusing on tactile inputs is associated with a larger activation of parietal cortex in blind than in sighted individuals (Burton, Sinclair, & Dixit, 2010;Burton, Sinclair, & McLaren, 2004;Burton, Snyder, Diamond, & Raichle, 2002). Reorganizational effects as a result of visual experience have nevertheless also been demonstrated in other structures involved in orienting behaviors, such as, for example, the superior colliculi (e.g., Tamietto et al, 2010; for evidence from animal studies, see also Carrasco & Pallas, 2006;Royal et al, 2010;Wallace et al, 2004), and the frontal eye fields (Garg, Schwartz, & Stevens, 2007).…”
Section: Auditory Tactile and Audiotactile Attentionsupporting
confidence: 71%
“…Several studies have reported that the occipital cortex of CB responds quite indifferently to a variety of cognitive tasks, suggesting that some common factors (i.e., attentional) rather than specific cognitive processes may contribute to the unselective occipital activity observed in this population (5)(6)(7)(8). In contrast, other studies do suggest that distinct regions of the visually deprived occipital cortex may show functional specialization that is to some extent comparable to what is known in SI (9).…”
mentioning
confidence: 88%